Prevalence of Postmenopausal Symptoms, Its Effect on Quality of Life and Coping in Rural Couple - Shukla, Radha (J Midlife Health, 2018)
AIM: Menopause is a physiological process, with potential to lead to various pathological/psychological complications, leading to change in quality of life (QOL). Although literature suggests the effect of menopause on various aspects of life, there is scarcity of studies from rural setup in this regard. Thus, it is essential to assess extent of menopause-related changes, its awareness, and coping mechanisms in rural couple. This study aimed to find the prevalence of postmenopausal symptoms, its severity, and effect on QOL of rural women and the couples' coping mechanisms. MATERIALS AND METHODOLOGY: A cross-sectional survey was conducted by approaching 250 families from two villages of Gujarat, India. Inclusion criteria were any woman having attained menopause naturally within last 10 years and having her husband available for data collection. Hundred such couples consenting for participation were included in the study. Data on demographic variables, menopause-specific QOL, personal health of women, and coping of the couple were collected. RESULTS: The prevalence of menopausal symptoms was found to be 47%. Mean (standard deviation) age at menopause was 44.9 (4.9) years. The prevalence of at least one symptom related to vasomotor was 21.3%, physical 91.5%, psychosocial 44.7%, and sexual was 0%. “QOL and Bother” analysis revealed that all those with menopausal symptoms also had their QOL affected from mild-to-moderate extent. The husbands of women with menopausal symptoms were aware of their condition; however, neither of them exhibited use of the active coping mechanism. The avoidant emotional coping strategy appeared to be followed by most. CONCLUSION: Couples were found to be aware of menopause; however, the symptoms arising as consequence of it seem to be accepted as natural age-related changes. This could possibly account for not taking any active coping strategy despite reporting of mild-to-moderate botheration by women and awareness in both. Rigorous health education and awareness about menopausal changes might be beneficial.